Effect of corneal cross-linking on biomechanical changes following transepithelial photorefractive keratectomy and femtosecond laser-assisted LASIK - Chen, Wen; Bao, FangJun; Roberts, Cynthia J.; Zhang, Jia; Wang, Chong; Li, XueFei; Wang, JunJie; Abu Said, Anas Ziad Masoud; Mayopa, Kevin Nguelemo; Chen, YaNi; Zheng, XiaoBo; Eliasy, Ashkan; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: To evaluate the change in corneal biomechanics in patients with postoperative ectasia risk when combining two common laser vision correction procedures (tPRK and FS-LASIK) with cross-linking (in tPRK Xtra and FS-LASIK Xtra). Methods: The study included 143 eyes of 143 myopic, astigmatic patients that were divided into non-cross-linked refractive surgery groups (non-Xtra groups, tPRK and FS-LASIK) and cross-linked groups (Xtra groups, tPRK Xtra and FS-LASIK Xtra) according to an ectasia risk scoring system. The eyes were subjected to measurements including the stress-strain index (SSI), the stiffness parameter at first applanation (SP-A1), the integrated inverse radius (IIR), the deformation amplitude at apex (DA), and the ratio of deformation amplitude between apex and 2 mm from apex (DARatio2mm). The measurements were taken preoperatively and at 1, 3, and 6 months postoperatively (pos1m, pos3m, and pos6m). Posterior demarcation line depth from the endothelium (PDLD) and from the ablation surface (DLA) were recorded at pos1m. Results: SP-A1 significantly decreased, while IIR, deformation amplitude, and DARatio2mm increased significantly postoperatively in all four groups (p < 0.01)—all denoting stiffness decreases. In the FS-LASIK group, the changes in IIR, DA, and DARatio2mm were 32.7 ± 15.1%, 12.9 ± 7.1%, and 27.2 ± 12.0% respectively, which were significantly higher (p < 0.05) compared to 20.1 ± 12.8%, 6.4 ± 8.2%, and 19.7 ± 10.4% in the FS-LASIK Xtra group. In the tPRK group, the change in IIR was 27.3 ± 15.5%, significantly larger than 16.9 ± 13.4% in the tPRK Xtra group. The changes of SSI were minimal in the tPRK (−1.5 ± 21.7%, p = 1.000), tPRK Xtra (8.4 ± 17.9%, p = 0.053), and FS-LASIK Xtra (5.6 ± 12.7%, p = 0.634) groups, but was significant in the FS-LASIK group (−12.1 ± 7.9%, p < 0.01). After correcting for baseline biomechanical metrics, preoperative bIOP and the change in central corneal thickness (△CCT) from pre to pos6m, the changes in the IIR in both FS-LASIK and tPRK groups, as well as DA, DARatio2mm and SSI in the FS-LASIK group remained statistically greater than their corresponding Xtra groups (all p < 0.05). Most importantly, after correcting for these covariates, the changes in DARatio2mm in the FS-LASIK Xtra became statistically smaller than in the tPRK Xtra (p = 0.017). Conclusion: The statistical analysis results indicate that tPRK Xtra and FS-LASIK Xtra effectively reduced the biomechanical losses caused by refractive surgery (tPRK and FS-LASIK). The decrease in corneal overall stiffness was greater in FS-LASIK than in tPRK, and the biomechanical enhancement of CXL was also higher following LASIK than after tPRK.